A case study on sibling relational problem : its clinical significance in managing a dyslexic adolescent with mild depressive disorder - Anuradha Thiagarajan,; Noor Azimah Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this case study was to see the impacts of managing sibling relational problem on mild depressive disorder. This approach was applied on a 15-year-old girl, who has dyslexia. She was found to have mild depression for one year that was precipitated by her poor relationship with her younger sibling. The intervention used in managing this case was adapted from the Siblings Are Special Module, a special programme that helps to alleviate anger and frustration that siblings had on each other. These 5 session interventions also included leisure activities that helped them to overcome their ongoing conflicts and were conducted over 3 months period. Parents were involved in the last 2 sessions in order to promote positive parenting. She showed a marked improvement in her psychological wellbeing and family relationship especially with her siblings at the end of the intervention. In conclusion, the intervention used to improve sibling relationship has shown to be effective in improving the mental health of the adolescents.